2021
DOI: 10.1155/2021/6646272
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Shrinkage of Ultrahigh‐Performance Concrete Containing Lithium Carbonate and Nano‐Calcium Carbonate

Abstract: Early strength generation is essential for the successful application and usage of Ultrahigh-Performance Concrete (UHPC) in reinforcing concrete structures. The work contained in this paper focused on evaluating the effects of lithium carbonate (Li2CO3, denoted as LC) and nano-calcium carbonate (NC) on the early mechanical properties and autogenous shrinkage of UHPC under normal temperature curing conditions. In the study, scanning electron microscope (SEM) was utilized to investigate and quantify the morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…T. Wang et al [ 78 ] concluded that the 1-day combined strength of UHPC increased significantly with increasing amounts of Li 2 CO 3 and NC, and that NC was effective in mitigating the loss of the 28-day combined strength of UHPC. After modification, the UHPC combined strength and flexural strength increased by about 68% and 38%, respectively, over the control sample.…”
Section: The Effect Of Nano-sio 2 and Nano-caco ...mentioning
confidence: 99%
“…T. Wang et al [ 78 ] concluded that the 1-day combined strength of UHPC increased significantly with increasing amounts of Li 2 CO 3 and NC, and that NC was effective in mitigating the loss of the 28-day combined strength of UHPC. After modification, the UHPC combined strength and flexural strength increased by about 68% and 38%, respectively, over the control sample.…”
Section: The Effect Of Nano-sio 2 and Nano-caco ...mentioning
confidence: 99%
“…Furthermore, the mechanical properties of cementitious materials with LS incorporation have been thoroughly investigated, thus encompassing parameters like compressive strength [ 50 , 51 ], tensile strength [ 52 , 53 ], elastic modulus [ 54 ], and flexural strength [ 49 ]. Moreover, the durability of LS-based cementitious composites has received significant attention, including studies on chloride migration [ 55 , 56 ], sulfate attack [ 57 , 58 ], shrinkage [ 56 , 59 ], freeze–thaw resistance [ 57 ], acid corrosion [ 60 ], and creep [ 50 ]. Furthermore, the utilization of LS in the construction materials industry not only mitigates environmental pollution but also significantly enhances economic benefits.…”
Section: Introductionmentioning
confidence: 99%